Methodological Approaches to Labor Norming in Scholarly Research and Development - Gasanov, S.S.; Kotlyarevsky, Ya.V.; Melnikov, O.V.; Kniaziev, S.I.; Shtangret, A.M.; Semenyuk, E.P. (Science and Innovation, 2024)
Introduction. Research and development (R&D) activities are sophisticated and multifaceted type of human labor that has a creative component, so the problem of its norming is a very complex and, at the same time, extremely important issue in the light of modern paradigm of the widest possible introduction of innovations in socio-economic processes. Problem Statement. The authors proceed from the fact that labor in R&D is internally heterogeneous with a particularly important creative research component. Therefore, based on qualitatively and quantitatively related phenomena of coordination of scholarly research organizational issues in terms of planning, organization, and conduct of R&D activities, while considering methodological and empiric aspects of structural and systemic factors, based on in-house experience and applied approaches that have been implemented in sectoral legislation, they have offered a concept of prospects for further research in the sphere of norming of scholarly research labor. Purpose. The purpose is to contribute to elaborating methodological approaches to labor norming in scholarly research and development. Materials and Methods. Analytical processing of applicable regulations and scholarly research publications in order to develop approaches to norming scholarly research labor. Results. The authors consider that despite, in general, each R&D work is unique, there are elements that are common for all researches in different qualitative and quantitative combinations, in all types of scholarly research activities. In other words, all common elements, i.e. the basic activities, can be normalized based on unified coordinated system that takes into account a broad range of peculiarities, structures, and contents of scholarly research labor with consideration of differential need in creating new knowledge resulting from R&D activities. Theoretical and applied generalization presented by the authors facilitates the formation of a systemic and structural model for scholarly research labor norming. Conclusions. The obtained results can be the starting point for further improvement of the regulation of R&D sphere in the context of reforming the activities of Ukrainian higher educational establishments and R&D institutions.